IMPLEMENTASI LATIHAN PERNAPASAN DAN AROMATERAPI SERAI PADA KUALITAS TIDUR LANSIA DIABETES MELLITUS - Fina Zulfa Ramadani; Nurul Hidayah; Lucia Retnowati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Older adults living with diabetes mellitus face a heightened chance of poor sleep because of age-related physiological shifts alongside disease symptoms such as frequent urination and nerve-related discomfort. A non-drug approach that may support better rest is the combined use of breathing exercises and lemongrass aromatherapy. This case study set out to describe sleep patterns among elderly diabetic individuals before and after receiving this combined intervention. The exploratory case study involved two older subjects residing in Sumberporong Village, Lawang Subdistrict, carried out between 21 and 28 April 2026. Sleep condition was assessed with the Pittsburgh Sleep Quality Index (PSQI), while adherence to the intervention was tracked through an observation checklist. Findings revealed that, prior to treatment, Subject 1 recorded a PSQI value of 9 and Subject 2 a value of 8, both falling into the poor-sleep category. Across five consecutive days, participants performed slow breathing exercises (5–10 repetitions per session) together with 10–15 minutes of inhaled lemongrass aromatherapy; observation scores rose from 21 to 30 for Subject 1 and from 18 to 28 for Subject 2. Following the intervention period, PSQI values fell to 6 for Subject 1 and 7 for Subject 2, marking reductions of three and one points respectively. The study concludes that pairing breathing exercises with lemongrass aromatherapy shows promise for enhancing sleep quality among elderly people with diabetes mellitus.